Number theory and cryptography : papers in honor of Johannes Buchmann on the Occasion of His 60th Birthday - Katzenbeisser, Stefan (Lecture Notes in Computer Science,, 2013)
This festschrift, published in honor of Johannes Buchmann on the occasion of his 60th birthday, contains contributions by some of his colleagues, former students, and friends. The papers give an overview of Johannes Buchmann's research interests, ranging from computational number theory and the hardness of cryptographic assumptions to more application-oriented topics such as privacy and hardware security. With this book we celebrate Johannes Buchmann's vision and achievements.